Perspektif Mahasiswa Bekerja di Bidang Pertanian sebagai Upaya Peningkatan Pembangunan SDM Indonesia - Achmad Kharisudin; Putra Irwandi (Sigmagri, 2022)
Abstrac The agricultural sector is a sector that contributes almost half of the Indonesian economy. Based on data from BPS for 2019-2020, the agricultural sector provides food for more than 270 million people and dominates as a source of income in Indonesia by 33.4 million (27.33%). The high opportunity and prospect of working in agriculture, unfortunately, is followed by the phenomenon of the interest of the younger generation to work in this sector, resulting in a decline in the regeneration of future young farmers. In addition, it also has an impact on reducing the demand for learning of the younger generation in the field of agricultural science. The low interest of the younger generation to work in agriculture is caused by several factors, including the perception that the agricultural sector is less promising in the future, the lack of prestige of relatively low salaries, the existence and influence of social strata in the community. This research was conducted using a structured quantitative survey method to produce descriptive data and conclusive findings that are descriptive. The research was conducted on students of the Faculty of Agriculture, Universitas Brawijaya majoring in Agroecotechnology and Agribusiness. The number of participants consisted of 100 people with diverse family backgrounds to find out the different perceptions of working in the agricultural sector. ABSTRAK Bidang pertanian merupakan sektor yang memberikan sumbangsih hampir setengah perekonomian Indonesia. Berdasarkan data dari BPS tahun 2019-2020, sektor pertanian menyediakan makanan lebi dari 270 juta masyarakat dan mendominasi sebagai mata pencahaian di Indonesia sebesar 33, 4 juta (27,33%). Tingginya peluang dan prospek bekerja di bidang pertanian, sayangnya diikuti oleh fenomena minat generasi muda untuk bekerja di sektor ini sehingga mengakibatkan regenerasi petani muda masa depan menjadi menurun. Selain itu, juga berdampak pada penurunan minta belajar generasi muda terhadap bidang ilmu pertanian. Rendahnya ketertarikan generasi muda bekerja di bidang pertanian disebabkan oleh beberap faktor antara lain persepsi bidang pertanian kurang menjanjikan di masa depan, kurang bergengsim gaji yang realtif rendah, eksistensi dan pengaruh strata sosial di lingkungan masyarakat. Penelitian ini dilakukan dengan menggunakan metode survey kuantitatif tersturktur guna menghasilkan data deskriptif dan temuan konklusif yang bersifat deskriptif. Penelitian dilakukan kepada mahasiswa Fakultas Pertanian Universitas Brawijaya jurusan Agroekoteknologi dan Agribisnis. Jumlah partisipan terdiri dari 100 orang dengan latar belakang keluarga yang beragam guna mengetahui perbedaan persepsi bekerja di bidang pertanian.